Augmenting melodic intonation therapy with non-invasive brain stimulation to treat impaired left-hemisphere function: two case studies - Al-Janabi, Shahd; Nickels, Lyndsey A.; Sowman, Paul F.; Burianová, Hana; Merrett, Dawn; Thompson, Bill (Frontiers in Psychology, 2014)
The purpose of this study was to investigate whether or not the right hemisphere can be engaged using Melodic Intonation Therapy (MIT) and excitatory repetitive transcranial magnetic stimulation (rTMS) to improve language function in people with aphasia. The two participants in this study (GOE and AMC) have chronic non-fluent aphasia. A functional Magnetic Resonance Imaging (fMRI) task was used to localize the right Broca’s homologue area in the inferior frontal gyrus for rTMS coil placement. The treatment protocol included an rTMS phase, which consisted of 3 treatment sessions that used an excitatory stimulation method known as intermittent theta burst stimulation, and a sham-rTMS phase, which consisted of 3 treatment sessions that used a sham coil. Each treatment session was followed by 40 minutes of MIT. A linguistic battery was administered after each session. Our findings show that one participant, GOE, improved in verbal fluency and the repetition of phrases treated with MIT in combination with TMS. However, AMC showed no evidence of behavioural benefit from this brief treatment trial. Post-treatment neural activity changes were observed for both participants in the left Broca’s area and right Broca’s homologue. These case studies indicate that a combination of rTMS applied to the right Broca’s homologue and MIT has the potential to improve speech and language outcomes for at least some people with post-stroke aphasia.